Can occupational skills explain the gender wage gap in a developing economy? An unconditional quintile regression approach - Zubaria Andlib (Global Labor Organization (GLO), 2025)
There are many factors behind the persistent gender wage gap in a in developing economy, such as gender discrimination, occupational segregation, social norms, and attitudes. To close the gender wage gap, it is mandatory to create gender-inclusive work environments, increase minimum wages and implement labour market regulations. The present study investigates the gender wage gap for four occupational groups based on skill levels as per ISCO-8 guidelines in case of a developing economy Pakistan. The study has utilized the latest available Labour Force Survey (2020-21) data and applied the Oaxaca-Blinder decompositions and unconditional quantile regressions. The empirical outcome described that women earn lower wages in low and average-skill occupations; however, in high and very-high skilled occupations, women are in advantageous positions. In addition, the empirical estimation elaborates the presence of glass ceiling effects in low, average and very high skill levels of occupations in case of a developing economy, Pakistan. To address the issue of the gender wage gap, governments, employers, and society must undertake a collective effort to achieve equal pay for equal work and provide adequate career opportunities in high skill occupations for women in developing economies.
Keywords: J08; J24; J31; 330; Gender wage gap; skill levels; occupations; glass ceiling